Virtual reality tool for learning sign language in spanish (2020)
Language is the means of human access to the world. Languages have the virtue of opening up alternative ways of thinking and understanding the place people inhabit, relating to it, expanding it and modifying it. As a possibility of communication, languages open up opportunities to relate to other people, to get closer to them and to develop a broader understanding of the social and the human elements [1]. This research presents a visual tool designed to allow the learning of multiple words that are part of Spanish Sign Language (SSL) through an anthropomorphic model that is completely manipulable and programmable.